THE CENTRAL TRUTH OF HINDUISM - Sanjyot D. Pai Vernekar (Journal of Dharma, 2004)
The closing quarter of the twentieth century witnessed the emergence of numerous forms of religious fundamentalism in Asia, in general, and in the Indian subcontinent, in particular. In consequence, the commencement of the twenty-first century had to be characterised by a re-initiation of public debate on the nature, significance and function of religion. As of today, the debate is being carried out as much within India as it is in quite a few other countries of the subcontinent. The contemporary scenario of the debate in India is with reference to so-called Hindutva as the sheet anchor of Hinduism. In view of this, it is quite in place to attempt a re-examination of the current concept of religion, in general, and of the Indian religion, in particular.